ISTEM PENUNJANG KEPUTUSAN PENGUKURAN KINERJA KARYAWAN MENGGUNAKAN METODE ANALYSIS HIERARCHY PROSES PADA PT. NSC FINANCE MARISA - Karim, Jorry (Teknosains: Media Informasi Sains dan Teknologi, 2016)
Measurement of the performance of a company is very important to evaluate and plan for the future. Absolute performance appraisal should be done to determine the performance of each employee to be achieved. For that each company has a different way of assessing employee performance. In practice, the assessment of the performance of the employees should be done with a good and appropriate methods, so there is no error in judgment. The results of the assessment should be done to ensure a fair and satisfactory treatment for employees who are assessed, so that in turn foster loyalty and morale. There are several tools that are commonly used for measuring the performance of employees, namely Decision Support System Analysis method Hierarchy Process (AHP). Decision support system is a tool that can be used to assess employee performance by comparing criteria and alternatives employees. This research was built using the MySQL database, and using Dreamweaver for web development, and PHP programming language.